Evaluasi Pengelolaan Embung di Kabupaten Sleman, Daerah Istimewa Yogyakarta - Wilopo, Wahyu; Setiawan, Hendy; Eka Putra, Doni Prakasa (Universitas Diponegoro, 2020)
The Indonesian government has promoted reservoir (embung) development programs throughout Indonesia. This program is primarily designed at supporting agricultural irrigation, especially in the dry season. However, in its implementation, there are often many obstacles both in technical and management, causing the main purpose of the reservoir construction cannot be achieved optimally. Therefore, this study aims to evaluate the condition of the reservoir located in Sleman Regency, Yogyakarta Special Region, in terms of physical, institutional, and management constraints. The study was conducted through a direct survey of 9 reservoirs and interviews with managers and residents around the reservoir. The results showed that two reservoirs have small damage in the reservoir building, three reservoirs do not yet have managers, and three reservoirs have not functioned following the purpose of reservoirs development. The obstacle often found in managing reservoirs is the unclear structure for the management of the reservoir, and the existing management is not effectively working. Therefore, the regulation of using reservoir water is not available. It is necessary to have a management organization involving the community and village government where the reservoir is located and also community beneficiaries of agricultural irrigation to guarantee its function and sustainability.